Penalty Clauses through the Lens of Unconscionability Doctrine: Birch v. Union of Taxation Employees, Local 70030 - Davis, Kevin (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
The author reviews the recent case of Birch v. Union of Taxation Employees, Local 70030, in which the Ontario Court of Appeal evaluated—in terms of the doctrine of unconscionability—the enforceability of a clause fining union members who cross picket lines during legal strikes. He applauds the decision as an important step toward jettisoning the traditional common law penalty doctrine, according to which stipulated remedy clauses designed to have an in terrorem effect upon a contracting party are per se unenforceable. The author criticizes the decision, however, for its failure to examine features of the case that would have been ignored under the penalty doctrine but that should have been prominent under the unconscionability doctrine. These features include: other provisions of the contract, the relative difficulty of arriving at “a genuine pre-estimate of the loss” as opposed to a “reasonable penalty”, and the process by which the contract was formed. The author concludes that, in failing to examine these features, the court missed an opportunity to clarify the changing law on the enforceability of stipulated remedy clauses.